Does non-conventional education investment make profitable private return in Malaysia? - Loganathan, Nanthakumar; Mohd Noor, Zaleha; Abdul Jalil, Suhaila (Canadian Center of Science and Education, 2010)
This study provides estimates of the private returns of tertiary non-conventional education (NCE) for management graduates in Malaysia. The term ‘non-conventional education’ used in this research refers to distance learning and part-time management degree program graduates. We evaluate the private returns using basic concept of educational cost and benefit analysis. The data used were derived from alumni dataset from Universiti Putra Malaysia (UPM) and National University of Malaysia (UKM) alumni division. Calculating the private returns of lifetime earnings, we find that the internal rates of return for NCE graduates are similar in both public and private sectors. Nevertheless, the results presented in this study are the first approximation ever of the private rate of returns to NCE in Malaysia, based on surveys on management NCE graduates in the Malaysian labor market. This study also seeks to contribute to the existing knowledge of economic analysis on lifelong learning in Malaysia.